Estimating the Cost of Emissions at Toll Booths: Case Study of Tema and Frafraha Toll Booths in the Greater Accra Region of Ghana. - Adu-Ababio, K. (University of Ghana, 2015)
Global demand for easy mobility is increasing and the environmental impact of transport has become an important concern in transportation network planning and decision-making. As a result suitable methods are required to assess fuel consumption and emissions reduc-tion strategies that seek to improve energy efficiency and decarbonisation. This thesis looks at the contribution of toll plazas to transport CO2 emissions as it is at these specific loca-tions that bottlenecks and congestion usually occur. Using a mechanical formula and an integrated methodology, this study specifically analyses the influence of waiting time at Manual Toll Collection (MTC) stations on energy consumption and subsequent excess CO2 emissions at the Accra/Tema-bound and the Oyibi/Frafraha bound toll plazas in the Greater Accra region of Ghana by considering five vehicle categories. Excess CO2 emissions ob-tained is measured in tons (tCO2) and valued in terms of Carbon Credits to obtain monetary estimates in Dollars. Case studies shows that energy consumption and CO2 emissions are directly related to vehicle mass, engine efficiency, acceleration rate and the amount of waiting time. Articulator/Heavy Trucks records the highest per vehicle excess CO2 emis-sions rate of 2.905 tCO2 and 0.953 tCO2 for the Frafraha and the Tema bound toll plazas respectively whiles the Saloon car category recorded the least per vehicle excess emissions of 0.162 tCO2 and 0.054 tCO2 for the Frafraha and the Tema toll plazas respectively. Cost-ing results also show that Ghana can earn some amount of money in Carbon Credits for all vehicle categories considered. Per vehicle excess CO2 emissions from Articulated/Heavy Trucks values highest - $36.95 and $12.12 at the Frafraha and the Tema toll plazas respec-tively whiles the Saloon car category excess CO2 emissions values least - $2.06 and $0.69 at the Frafraha and the Tema toll plaza respectively. To achieve these monetary gains and ensure transport sustainability, the study suggests that the application of new technologies like the Intelligent Transport Systems (ITS) to toll collection systems is an effective man-agement strategy from an environmental point of view to tackle the issue of excess CO2 emissions at toll plazas.
Thesis (MPhil) - University of Ghana, 2015
Keywords: Cost; Emissions; Mobility; Demand